Hidden in Plain Sight: Seeing the Stripping of Jesus as Sexual Violence - David Tombs (University of Sheffield, 2020)
Recent work in biblical studies has given increased attention to a reading of Jesus as a victim of sexual abuse. This article explores how the stripping of Jesus might be understood as an example of abuse ‘hidden in plain sight’. Most students are initially surprised or doubtful when it is suggested that Jesus is a victim of sexual violence. However, this scepticism can become a powerful learning resource if they are helped to ‘discover’ it for themselves through an experiential learning process. This might involve a critical examination of crucifixion and stripping images, and/or a contextual bible study on Matthew 27:26–31. Discovering the sanitising and erasure of sexual violence in the dominant (mis)understanding of crucifixion can offer students insight into other ways that past and present sexual violence is often marginalised, normalised, or hidden. Often these classroom exercises prompt a discussion of what makes abuse ‘sexual abuse’.